Anti-dripping ABS (Acrylonitrile Butadiene Styrene) composite material and preparation method and application thereof
By using a combination of ultra-high molecular weight styrene-acrylonitrile copolymer and bromine flame retardant in ABS composites, the problem of improving flame retardant and drip resistance of ABS materials is solved, and efficient flame retardant and drip resistance is achieved, while avoiding the environmental protection problems of polytetrafluoroethylene.
Patent Information
- Application Number
- CN202411979986.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, there is relatively lack of technology to improve the flame retardant and drip resistance of ABS resin materials instead of adding polytetrafluoroethylene, and polytetrafluoroethylene has environmental protection problems.
Ultra-high molecular weight styrene-acrylonitrile copolymer is used as anti-drip agent, combined with bromine flame retardant, and network structure is formed to improve the anti-drip and flame retardant properties of ABS composites.
The drip resistance and flame retardant properties of ABS composites have been significantly improved, and the continuous combustion drip time has reached more than 34 seconds, the flame retardant level has reached V-0 or above, while maintaining good toughness.
Smart Images

Figure BDA0005221317850000071 
Figure BDA0005221317850000072 
Figure BDA0005221317850000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of engineering plastics, and more specifically to an anti-drip ABS composite material and a preparation method and application thereof. Background Art
[0002] ABS (Acrylonitrile-Butadiene-Styrene) is a thermoplastic polymer material with high strength, good toughness and easy processing. Compared with SAN (Acrylonitrile-Butadiene), ABS has a wider range of applications because it has better toughness.
[0003] The polar oxygen index of ABS is only 18-20, and it is a flammable polymer material. When ABS is used in the housing of electrical equipment that requires electrical insulation and flame retardancy, it needs to be flame retardant and anti-dripping modified. Adding flame retardants is a simple and efficient way to achieve flame retardant modification of ABS. The commonly used flame retardants in ABS are brominated flame retardants. However, the flame retardant performance of ABS with only brominated flame retardants is limited, and the anti-dripping performance is poor.
[0004] At present, the main method is to add polytetrafluoroethylene to further improve the flame retardant properties and achieve anti-dripping, such as the Chinese patent named a highly heat-resistant flame-retardant ABS material. Its main principle is to use polytetrafluoroethylene to be stretched and fibrillated to form a fibril network. ABS can be netted by the fibril network without dripping when burning, and bromine flame retardants synergistically improve the flame retardant grade. However, polytetrafluoroethylene is a polyfluoroalkane compound (PFOA). PFOA has high stability and is difficult to degrade in nature. It has strong bioaccumulation. Because this type of substance is persistent and difficult to degrade, it will accumulate in the body after being absorbed by the human body and organisms, interfering with the endocrine system and affecting normal reproduction and metabolism. As people realize the hazards of PFOA, governments of various countries have begun to introduce policies and regulations to restrict its production and use. Therefore, it is necessary to develop other synergistic flame retardant technologies and anti-dripping technologies for replacing polytetrafluoroethylene for ABS materials. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the problem that there is a lack of technology to replace the addition of polytetrafluoroethylene to improve the synergistic flame retardant technology and anti-drip performance of ABS resin materials, and to provide an anti-drip ABS composite material.
[0006] A further object of the present invention is to provide a method for preparing the above ABS composite material.
[0007] A further object of the present invention is to provide the use of the above ABS composite material in the preparation of household appliances, electronic appliances or office supplies.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] An anti-drip ABS composite material comprises the following components in parts by weight:
[0010] ABS resin 58-76 parts,
[0011] 10-22 parts of brominated flame retardant,
[0012] 3 to 16 parts of anti-dripping agent;
[0013] The anti-dripping agent is an ultra-high molecular weight styrene-acrylonitrile copolymer, and the weight average molecular weight of the anti-dripping agent is ≥2×10 6 g / mol.
[0014] The weight average molecular weight of conventional styrene-acrylonitrile copolymer is 0.5×10 5 ~3×10 5 The inventors of the present invention have found through research that the use of ultra-high molecular weight (weight average molecular weight ≥ 2×10 6 The styrene-acrylonitrile copolymer with a molecular weight of 100 g / mol is used as an anti-dripping agent. Its molecular chain is very long, and it is easy to be oriented by shearing and stretching during injection molding, and it is easy to overlap each other to form a network structure, and cooperate with the brominated flame retardant to improve the anti-dripping performance of the ABS composite material. At the same time, the addition of the ultra-high molecular weight styrene-acrylonitrile copolymer is also conducive to improving the flame retardant performance of the ABS composite material.
[0015] In the present invention, the weight average molecular weight of the styrene-acrylonitrile copolymer can be measured by gel permeation chromatography. The weight average molecular weight of the styrene-acrylonitrile copolymer can be specifically 2.0×10 6 , 2.5×10 6 , 3.0×10 6 , 3.5×10 6 , 3.8×10 6 4.2×10 6 , 4.5×10 6 , 4.8×10 6 , 5.0×10 6 , 5.5×10 6 , 6.0×10 6 , 6.5×10 6 , 6.8×10 6 , 7.0×10 6 , 7.5×10 6 , 7.8×10 6 8.0×10 6 g / mol, 8.5×10 6 , 8.7×10 6 g / mol or 9.0×106 The amount of styrene-acrylonitrile copolymer added can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 parts by weight or the range between any of the above values.
[0016] Preferably, the weight average molecular weight of the anti-dripping agent is 3.0×10 6 ~9×10 6 g / mol.
[0017] More preferably, the weight average molecular weight of the anti-dripping agent is 3.8×10 6 ~8.7×10 6 g / mol.
[0018] Further preferably, the weight average molecular weight of the anti-dripping agent is 5.7×10 6 ~8.7×10 6 By selecting the anti-drip agent with the weight average molecular weight, the obtained ABS composite material has better anti-drip performance.
[0019] Preferably, the acrylonitrile content of the styrene-acrylonitrile copolymer is 10-40 wt %, and the styrene content is 60-90 wt %.
[0020] In the present invention, the acrylonitrile content and the styrene content of the styrene-acrylonitrile copolymer can be obtained by testing the nitrogen content in the styrene-acrylonitrile copolymer by combustion elemental analysis and converting it.
[0021] The acrylonitrile content and the range of the styrene content of the styrene-acrylonitrile copolymer are the basis for selecting the preferred styrene-acrylonitrile copolymer for the performance of the ABS composite material, and are not intended to limit the styrene-acrylonitrile copolymer used in the present invention.
[0022] Preferably, the anti-drip ABS composite material comprises the following components in parts by weight:
[0023] ABS resin 69-74 parts,
[0024] 12 to 16 parts of brominated flame retardant,
[0025] Anti-dripping agent 6-15 parts.
[0026] By adjusting the amount of each component of the ABS composite material within this range, the anti-dripping performance is better.
[0027] In the present invention, ABS resin is used as the main resin, which accounts for more than 50wt% of the ABS composite material.
[0028] Preferably, the melt flow rate of the ABS resin at 220° C. and 10 kg load is 10 to 25 g / 10 min. The melt flow rate of the ABS resin is measured according to ISO1133-2011 standard.
[0029] Preferably, the average particle size of the rubber phase of the ABS resin is 200-1000 nm. The average particle size of the rubber phase can be measured and obtained by observation and statistics using a transmission electron microscope.
[0030] Preferably, the ABS resin has a butadiene content of 10 to 30 wt%, an acrylonitrile content of 15 to 30 wt%, and a styrene content of 40 to 75 wt%.
[0031] In the present invention, the butadiene content, acrylonitrile content and styrene content of the ABS resin can be obtained by testing the carbon, hydrogen and nitrogen content in the ABS resin by combustion element analysis and converting them.
[0032] The ranges of butadiene content, acrylonitrile content and styrene content of the above ABS resin are the basis for selecting the ABS resin with the preferred performance of the ABS composite material, and are not intended to limit the ABS resin used in the present invention.
[0033] Preferably, the brominated flame retardant is at least one of tetrabromobisphenol A, tris(tribromophenoxy)cyanurate, brominated epoxy oligomer or decabromodiphenylethane.
[0034] More preferably, the brominated flame retardant is at least one of tetrabromobisphenol A and tris(tribromophenoxy)cyanurate. By using the brominated flame retardant, the obtained ABS composite material has better anti-dripping performance.
[0035] Further preferably, the brominated flame retardant is tetrabromobisphenol A. By selecting the brominated flame retardant, the anti-dripping performance of the obtained ABS composite material is further improved.
[0036] Preferably, the ABS composite material further comprises 2 to 5 parts of a flame retardant synergist, more preferably 2 to 3 parts.
[0037] More preferably, the flame retardant synergist is an antimony-containing compound.
[0038] More preferably, the antimony-containing compound is at least one of antimony trioxide, antimony pentoxide or antimonate.
[0039] Preferably, the ABS composite material further comprises 2 to 10 parts of a toughening agent.
[0040] More preferably, the toughening agent is chlorinated polyethylene, polybutadiene grafted styrene-acrylonitrile copolymer (ABS high rubber powder), styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer or styrene-butadiene random copolymer.
[0041] Preferably, the ABS composite material further comprises 0.1 to 2 parts of other additives.
[0042] More preferably, the other auxiliary agent is at least one of an antioxidant, a lubricant or a weathering agent.
[0043] More preferably, the antioxidant is at least one of a hindered phenol antioxidant or a phosphate antioxidant.
[0044] Further preferably, the hindered phenol antioxidant is at least one of an alkyl monophenol antioxidant, an alkyl polyphenol antioxidant or a thiobisphenol antioxidant.
[0045] More preferably, the phosphate antioxidant is at least one of 2,4-di-tert-butylphenol (Irganox 168), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36) or 627A.
[0046] Further preferably, the lubricant includes but is not limited to stearamide lubricants.
[0047] Further preferably, the stearamide lubricant is at least one of EBS B50, EB-FF, EBSP400 or WK1890.
[0048] More preferably, the weathering agent is at least one of a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber, a triazine ultraviolet absorber or a hindered amine light stabilizer.
[0049] The preparation method of the above ABS composite material comprises the following steps:
[0050] The components are mixed uniformly, melted, extruded and granulated to obtain the ABS composite material.
[0051] The application of the above ABS composite material in the preparation of household appliances, electronic appliances or office supplies also falls within the protection scope of the present invention.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention adopts ultra-high molecular weight (weight average molecular weight ≥ 2×10 6The styrene-acrylonitrile copolymer with an ultra-high molecular weight of 1.4777 g / mol is used as an anti-dripping agent. Its molecular chain is very long and is easily oriented by shear and stretching during injection molding. It is easy to overlap with each other to form a network structure and cooperate with the brominated flame retardant to improve the anti-dripping performance of the ABS composite material (the continuous burning dripping time is more than 34s). At the same time, the addition of the ultra-high molecular weight styrene-acrylonitrile copolymer is also beneficial to the improvement of the flame retardant properties of the ABS composite material (the flame retardant grade reaches V-0 or above). In addition, controlling the amount of the ultra-high molecular weight styrene-acrylonitrile copolymer added can make the ABS composite material maintain good toughness (notch impact strength is 15.5kJ / m 2 above). DETAILED DESCRIPTION
[0054] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0055] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0056] ABS resin 1#: KF-730, melt flow rate at 220°C and 10kg load is 22g / 10min, produced by Liaoning Kingfa Technology Co., Ltd.;
[0057] ABS resin 2#: brand ABS 8434, melt flow rate at 220°C and 10kg load is 16g / 10min, produced by Shanghai Gaoqiao Co., Ltd.;
[0058] ABS resin 3#: brand name is ABS KF-718, melt flow rate at 220℃ and 10kg load is 12g / 10min, manufacturer is Liaoning Jinfa Technology Co., Ltd.;
[0059] Brominated flame retardant 1#: tris(tribromophenyl)cyanurate, commercially available;
[0060] Brominated flame retardant 2#: brominated epoxy oligomer, brand CXB-714C, manufactured by Korea Yujin Company;
[0061] Brominated flame retardant 3#: tetrabromobisphenol A, commercially available;
[0062] Phosphorus flame retardant: melamine polyphosphate, commercially available;
[0063] Flame retardant synergist: antimony trioxide, commercially available;
[0064] Anti-drip agent 1#: styrene-acrylonitrile copolymer, brand name HK-506, weight average molecular weight is about 5.7×10 6 g / mol, the manufacturer is Shandong Yuanbang New Materials Co., Ltd.;
[0065] Anti-drip agent 2#: styrene-acrylonitrile copolymer, brand name HK-507-1, weight average molecular weight is about 4.3×10 6 g / mol, the manufacturer is Shandong Yuanbang New Materials Co., Ltd.;
[0066] Anti-drip agent 3#: styrene-acrylonitrile copolymer, brand name HK-503, weight average molecular weight is about 7.8×10 6 g / mol, the manufacturer is Shandong Yuanbang New Materials Co., Ltd.;
[0067] Anti-drip agent 4#: styrene-acrylonitrile copolymer, brand name HK-507, weight average molecular weight is about 3.8×10 6 g / mol, the manufacturer is Shandong Yuanbang New Materials Co., Ltd.;
[0068] Anti-drip agent 5#: styrene-acrylonitrile copolymer, brand name HK-502, weight average molecular weight is about 8.7×10 6 g / mol, the manufacturer is Shandong Yuanbang New Materials Co., Ltd.;
[0069] Conventional molecular weight styrene-acrylonitrile copolymer: brand KFA-130, weight average molecular weight is about 9.3×10 4 g / mol, the manufacturer is Liaoning Jinfa Technology Co., Ltd.;
[0070] The weight average molecular weight of the above styrene-acrylonitrile copolymer is measured by gel permeation chromatography. The specific test conditions are: pretreatment: take a small amount of styrene-acrylonitrile copolymer and dissolve it in tetrahydrofuran for 12 hours, and filter it into the injection bottle by microporous filtration; the mobile phase is tetrahydrofuran, the test temperature is 40°C, the flow rate is 0.35mL / min, the standard sample is polystyrene, and the chromatographic column model is TSK gel Super Mutipore HZ-M*2.
[0071] Polyethylene: brand name is U050, weight average molecular weight is about 5 million, produced by Korea Petrochemical;
[0072] Polytetrafluoroethylene: brand name is X-010, produced by Shandong Dongyue Polymer Materials Co., Ltd.;
[0073] Toughening agent: Chlorinated polyethylene, IM500, Weifang Shandao Chemical Co., Ltd.;
[0074] Other additives 1#: The weight ratio of antioxidant to lubricant is 1:2. The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, commercially available; the lubricant is vinyl bisstearamide, commercially available;
[0075] Unless otherwise specified, the components (such as other auxiliary agent 1#) selected in each parallel example and comparative example are the same commercially available products.
[0076] The ABS composite materials provided in the embodiments and comparative examples of the present invention were tested for performance according to the following test methods:
[0077] Continuous burning dripping time: According to the vertical burning test in standard UL94-2018; the material is injection molded into a standard specimen (length 125mm, width 12.7mm, thickness 1.5mm) at 220℃. After being placed at room temperature for 24 hours, the standard specimen is continuously subjected to vertical burning until dripping occurs in the specimen, and the time from the application of flame to dripping is recorded.
[0078] Flame retardant grade: According to the standard UL94-2018 test for vertical combustion, the 1.5mm specimen should meet the V-0 grade requirements;
[0079] Izod notch impact strength: In accordance with GB1843-1996 "Plastic Izod Impact Test Method", the specimen is injection molded into 80×10×4mm and has a V-notch width of 8mm. The test pendulum energy is 2.75J and the test is conducted at room temperature.
[0080] The preparation process of the ABS composite material of each embodiment of the present invention and each comparative example is as follows: weigh each component according to the formula, put it into a high-speed mixer and mix it evenly, and then melt-extrude and granulate it through a twin-screw extruder to obtain an ABS composite material. Wherein, the screw speed is 400rpm, and the screw temperature of each section of the twin-screw extruder is set to 90°C for zone 1, 180°C for zone 2, 190°C for zone 3, 190°C for zone 4, 190°C for zone 5, 200°C for zone 6, 200°C for zone 7, 200°C for zone 8, 200°C for zone 9, and 210°C for zone 9 from the feed port to the die.
[0081] Examples 1 to 11
[0082] Examples 1 to 11 provide a series of ABS composite materials, the formulations of which are shown in Table 1.
[0083] Table 1 Formula of Examples 1 to 11 (parts by weight)
[0084]
[0085] Comparative Examples 1 to 6
[0086] Comparative Examples 1 to 6 provide a series of ABS composite materials, and their formulations are shown in Table 2.
[0087] Table 2 Formulas of Comparative Examples 1 to 6 (parts by weight)
[0088]
[0089]
[0090] The properties of the ABS composite materials of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 3.
[0091] Table 3 Performance test results of ABS composite materials of various embodiments and comparative examples
[0092]
[0093] From Table 3, we can see that:
[0094] The continuous burning dripping time of the ABS composite materials of Examples 1 to 11 is all above 34 seconds, and the flame retardant grades are all above V-0, indicating that the ABS composite materials of the present invention have good flame retardant properties and anti-dripping properties. In addition, the notched impact strength of the ABS composite materials of Examples 1 to 11 is all above 15.5 kJ / m 2 The above indicates that the ABS composite material of the present invention maintains good toughness.
[0095] Comparative Example 1 adds high molecular weight polyethylene, and the properties of the ABS composite material are relatively poor. Comparative Example 2 adds a small amount of polytetrafluoroethylene to make the flame retardant and anti-dripping properties of the ABS composite material equivalent to those of Example 1, but the selection of polytetrafluoroethylene has environmental issues. Comparative Example 3 adds too little high molecular weight styrene-acrylonitrile copolymer, the continuous burning dripping time of the ABS composite material is short, and the flame retardant grade is poor. Comparative Example 4 adds too much ultra-high molecular weight styrene-acrylonitrile copolymer, and the notched impact of the ABS composite material is very poor. Comparative Example 5 adds a phosphorus-based flame retardant, and the properties are poor. Comparative Example 6 adds a conventional molecular weight styrene-acrylonitrile copolymer, which cannot improve the anti-dripping and flame retardant properties of the ABS composite material.
[0096] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. An anti-drip ABS composite material, characterized in that: The composition comprises the following components in parts by weight: ABS resin 58-76 parts, 10-22 parts of brominated flame retardant, 3-16 parts of anti-dripping agent; The anti-dripping agent is an ultra-high molecular weight styrene-acrylonitrile copolymer, and the weight average molecular weight of the anti-dripping agent is ≥2×10 6 g / mol.
2. The ABS composite material according to claim 1, characterized in that: The melt flow rate of the ABS resin at 220° C. and a load of 10 kg is 10 to 25 g / 10 min.
3. The ABS composite material according to claim 1, characterized in that: The brominated flame retardant is at least one of tetrabromobisphenol A, tris(tribromophenoxy)cyanurate, brominated epoxy oligomer or decabromodiphenylethane.
4. The ABS composite material according to claim 1, characterized in that: The ABS composite material also includes 2 to 5 parts of a flame retardant synergist.
5. The ABS composite material according to claim 1, characterized in that: The ABS composite material also includes 2 to 10 parts of toughening agent.
6. The ABS composite material according to claim 1, characterized in that: The weight average molecular weight of the anti-dripping agent is 3.0×10 6 ~9×10 6 g / mol; preferably 3.8×10 6 ~8.7×10 6 g / mol; more preferably 5.7×10 6 ~8.7×10 6 g / mol.
7. The ABS composite material according to claim 1, characterized in that: The ABS composite material also includes 0.1 to 2 parts of other additives.
8. The ABS composite material according to claim 7, characterized in that: The other auxiliary agent is at least one of an antioxidant, a lubricant or a weathering agent.
9. The method for preparing the ABS composite material according to any one of claims 1 to 8, characterized in that: The steps include: The components are mixed uniformly, melted, extruded and granulated to obtain the ABS composite material.
10. Use of the ABS composite material according to any one of claims 1 to 8 in the preparation of household appliances, electronic appliances or office supplies.